Analisis Persepsi Guru menggunakan Smart LMS dengan Pendekatan Model Penerimaan Teknologi (TAM) - Nadya Faranda; Rayendra Rayendra; Ulfia Rahmi; Septriyan Anugrah; Indra Saputra (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the acceptance of the LMS Pintar Kemenag online training platform among public and private Madrasah Tsanawiyah teachers in Padang City using the Technology Acceptance Model (TAM). A quantitative survey was conducted involving 285 teachers, and the data were analyzed using descriptive statistics with SEMPLS. The results indicate high mean scores across all TAM constructs Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Behavioral Intention to Use showing a strong level of technology acceptance. Teachers consider the platform easy to operate and beneficial for professional development; consequently, they develop favorable attitudes and a sustained intention to use it for training and learning activities. These findings reinforce the relationship between perceived ease, perceived usefulness, and behavioral intention as proposed in TAM, while also highlighting the strategic role of digital platforms in supporting teacher competency development within religious education institutions. In conclusion, LMS Pintar Kemenag has been positively accepted by teachers, and its continued improvement is essential to enhance the effectiveness and sustainability of online professional training programs